IMPLEMENTASI PERATURAN DAERAH NO. 5 TAHUN 2016 TENTANG PERLINDUNGAN PEREMPUAN DAN ANAK DARI TINDAKAN KEKERASAN DI DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KOTA SEMARANG (DALAM FASILITASI PERLINDUNGAN PEREMPUAN DARI TINDAKAN KEKERASAN) - Shelma Janu Mahartiwi; Ari Subowo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
The policy of protecting women and children from acts of violence is one of the steps taken by the Semarang City government to prevent, facilitate, assist and deal with victims of violence especially women in order to get services related to the violence they experience. The services provided by the Government of Semarang City is the handling of complaints, medical services, psychological services and rehabilitation, legal aid and social reintegration. This policy is determined by the government of Semarang City which then appoints the Office of Women Empowerment and Child Protection which is assisted by several agencies and technical implementing units to decrease the number of violence against women which is increasing every year, so it is necessary to take the preventive action and handling the case so as not to more increasing. This research is a descriptive qualitative research that aims to know and analyze the process of policy implementation and the factors that inhibit. The theory used in this study is Merille S. Grindle, which states that in the implementation of a policy consists of two aspects namely view of the contents of policy and policy environment. The result of the research indicates that the existence of service and technical implementation unit, cases of violence against women can be known by the number of incoming complaints, but in the implementation of the policy is still hampered by some things such as lack of commitment and communication among members, lack of human resources, work and lack of organization of socialization to the community so that most people are not aware of the policy. It can be concluded that the implementation of the protection policy of women and children from acts of violence in the facilitation of women protection from acts of violence has not had a significant impact for the people of Semarang City since the violence is still high and increasing every year.